Foreign direct investment versus joint ventures - Li, Yuting (Kansas State University, 2011)
This paper studies economic factors that affect a multinational’s decision between serving a foreign market via foreign direct investment (FDI) and setting up a joint venture (JV) with a local firm in the host country. The factors that we consider include the substitutability of products produced by competing firms, as well as the hotly debated intellectual property rights (IPRs) protection. In a simple North-South framework, we show that JV is the equilibrium market structure when the degree of R&D spillover is moderate, products are considerably substitutable, and IPRs strong. The government of South needs to maintain a minimum level of IRP to encourage an effective JV. For increasing social welfare, the South also needs to have a policy that limits foreign ownership in a JV.
Keywords: Foreign direct investment; Joint ventre; Intellectual property rights; North-South trade; Economics (0501); Economic Theory (0511)